The Effects of the Endophytic Bacterium Pseudomonas fluorescens Sasm05 and IAA on the Plant Growth and Cadmium Uptake of Sedum alfredii Hance - Chen, Bao; Luo, Sha; Wu, Yingjie; Ye, Jiayuan; Wang, Qiong; Xu, Xiaomeng; Pan, Fengshan; Khan, Kiran Y.; Feng, Ying; Yang, Xiaoe (Frontiers in Microbiology, 2017)
Endophytic bacteria have received attention for their ability to promote plant growth and enhance phytoremediation, which may be attributed to their ability to produce indole-3-acetic acid (IAA). As a signal molecular, IAA plays a key role on the interaction of plant and its endomicrobes. However, the different effects that endophytic bacteria and IAA may have on plant growth and heavy metal uptake is not clear. In this study, the endophytic bacterium Pseudomonas fluorescens Sasm05 was isolated from the stem of the zinc (Zn)/cadmium (Cd) hyperaccumulator Sedum alfredii Hance. The effects of Sasm05 and exogenous IAA on plant growth, leaf chlorophyll concentration, leaf Mg2+-ATPase and Ca2+-ATPase activity, cadmium (Cd) uptake and accumulation as well as the expression of metal transporter genes were compared in a hydroponic experiment with 10 μM Cd. The results showed that after treatment with 1 μM IAA, the shoot biomass and chlorophyll concentration increased significantly, but the Cd uptake and accumulation by the plant was not obviously affected. Sasm05 inoculation dramatically increased plant biomass, Cd concentration, shoot chlorophyll concentration and enzyme activities, largely improved the relative expression of the three metal transporter families ZRT/IRT-like protein (ZIP), natural resistance associated macrophage protein (NRAMP) and heavy metal ATPase (HMA). Sasm05 stimulated the expression of the SaHMAs (SaHMA2, SaHMA3, and SaHMA4), which enhanced Cd root to shoot translocation, and upregulated SaZIP, especially SaIRT1, expression to increase Cd uptake. These results showed that although both exogenous IAA and Sasm05 inoculation can improve plant growth and photosynthesis, Sasm05 inoculation has a greater effect on Cd uptake and translocation, indicating that this endophytic bacterium might not only produce IAA to promote plant growth under Cd stress but also directly regulate the expression of putative key Cd uptake and transport genes to enhance Cd accumulation of plant.